2019
DOI: 10.1111/cas.14182
|View full text |Cite
|
Sign up to set email alerts
|

Glutaminolysis‐related genes determine sensitivity to xCT‐targeted therapy in head and neck squamous cell carcinoma

Abstract: Targeting the function of membrane transporters in cancer stemlike cells is a potential new therapeutic approach. Cystine‐glutamate antiporter xCT expressed in CD44 variant (CD44v)‐expressing cancer cells contributes to the resistance to oxidative stress as well as cancer therapy through promoting glutathione (GSH)‐mediated antioxidant defense. Amino acid transport by xCT might, thus, be a promising target for cancer treatment, whereas the determination factors for cancer cell sensitivity to xCT‐targeted thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…Currently, little is known about the relationship between typical stemness markers and the regulation of CSC metabolism, but researchers have shown that the stem cell marker CD44 may be crucial in the regulation of glycolytic metabolism[ 142 , 143 ]. The direct interaction between CD44 and the GSH transporter--solute carrier family 7 member 11 has been reported in multiple PDT articles[ 144 , 145 ], also suggesting the ability of PDT to manipulate CSCs through redox and energy metabolism.…”
Section: Impact Of Ros From Pdt On Cscsmentioning
confidence: 96%
“…Currently, little is known about the relationship between typical stemness markers and the regulation of CSC metabolism, but researchers have shown that the stem cell marker CD44 may be crucial in the regulation of glycolytic metabolism[ 142 , 143 ]. The direct interaction between CD44 and the GSH transporter--solute carrier family 7 member 11 has been reported in multiple PDT articles[ 144 , 145 ], also suggesting the ability of PDT to manipulate CSCs through redox and energy metabolism.…”
Section: Impact Of Ros From Pdt On Cscsmentioning
confidence: 96%
“…Glutamine contributes to the synthesis of α-ketoglutarate (α-KG) via its conversion to glutamate, thereby promoting the tricarboxylic acid (TCA) cycle and the synthesis of nucleotides required for cellular proliferation (27,29). CD44 variant (CD44v)-positive cancer stem-like cells (CSCs) express high levels of xCT and ASCT2, which promote GSH synthesis from cysteine and α-KG from glutamine, respectively (30). Because c-Myc regulates amino acid transporters such as ASCT2 (23), c-Myc is likely to induce metabolic reprogramming in CD44v-positive CSCs.…”
Section: Metabolic Reprogramming Through the Regulation Of Amino Acidmentioning
confidence: 99%
“…Indeed, in 1988 Bannai reported glutamine import via ASCT2 and conversion into glutamate that is exported in exchange of cystine import (1:1) via xCT (45). Yet, more recently, a metabolomic analysis reveals the importance of glutamine uptake by ASCT2 and its conversion into ROSproducing intermediate metabolite α-Ketoglutarate as marker of sensitivity during sulfasalazine xCT-inhibition cell death in head and neck squamous cells carcinoma (46). Glutaminolysis was also reported to sensitize melanoma cells to ferroptosis (47).…”
Section: Glutathione-dependent Ferroptosismentioning
confidence: 99%